Comparison of different puncture needles used for endoscopic ultrasound-guided fine-needle biopsy of Gastrointestinal subepithelial lesions (≤ 2 cm) with respect to the adequacy of specimen collection: study protocol for a multicenter randomized prospective trial - Yasunobu Yamashita; Reiko Ashida; Toshio Shimokawa; Tetsuya Ikeda; Osama Inatomi; Takashi Ogura; Yuzo Kodama; Kotaro Takeshita; Mamoru Takenaka; Akiko Tsujimoto; Yoshiki Nakai; Yukihisa Fujinaga; et al. (Trials)
Abstract Background Gastrointestinal subepithelial lesions (SELs) range from benign to malignant. Endoscopic ultrasound (EUS)-guided fine-needle biopsy (EUS-FNB) is used widely for pathological diagnosis of SELs. Early diagnosis and treatment are important because all Gastrointestinal stromal tumors (GISTs) have some degree of malignant potential. Diagnosing SELs with EUS-FNB is more difficult than diagnosing other tumors because an accurate diagnosis of GIST requires a sufficient tissue sample for immunostaining, which is part of the diagnostic protocol. Moreover, EUS-FNB is less accurate for diagnosis based on samples from SELs measuring ≤ 2 cm. However, our retrospective study showed that more than 50% of patients with SELs ≤ 2 cm were diagnosed as GIST. Therefore, EUS-FNB needles are required with adequate sampling in SELs measuring ≤ 2 cm. Previously, we conducted a retrospective single-center study of SELs measuring ≤ 2 cm, and reported that EUS-FNB with a Fork-tip needle was superior to that with a Franseen needle in that the former acquires sufficient sample. This multicenter comparative open-label superiority study is designed to verify whether a 22G Fork-tip needle is superior to a 22G Franseen needle with respect to sample acquisition. Methods/design Present study will randomly assign for 110 patients (55 in the Fork-tip needle group and 55 in the Franseen needle group) with SELs measuring ≤ 2 cm, all of whom are managed at one of the 10 participating endoscopic centers. The primary endpoint evaluates the superiority of a 22G Fork-tip needle over a 22G Franseen needle for collection of an adequate tissue specimen at the first puncture. The secondary endpoints compare successful puncture rate, procedure completion rate, number of adverse events, diagnostic suitability of the first puncture specimen for GIST, and the number of punctures required until adequate specimen collection. Discussion The outcomes may provide insight into the optimal needle choice for diagnosis of SELs ≤ 2 cm, thereby aiding development of practice guidelines. Present study is expected to promote early definitive diagnosis of GISTs, thereby increasing the number of cases that can receive curative treatment and improving prognosis. Trial registration Japan Registry of Clinical Trials (JRCT; trial registration: jRCTs052230144). Registered December 13, 2023. (URL; https://jrct.niph.go.jp/re/reports/detail/76858 ).